Towards multicultural memory: struggles over a Muslim cemetery in post-civil war Asturias, Spain - Becker-Topkara, Elisabeth; Suárez-Collado, Ángela; Arana Barbier, Paula Maria (Ethnicities, 2025)
This article traces struggles over a Muslim cemetery in post-Civil War Asturias, Spain, highlighting the centrality of multicultural memory in creating an inclusive contemporary society. Drawing on theories of multiculturalism put forth by Civil Sphere Theory and the British School of Multiculturalism, we shed light on the bifurcating cultural narrative of the civil (victim) and uncivil (perpetrator) and its grasp on collective memory, complicating this still-dominant perspective through the ambivalent and unsettling role of the Moroccan Muslim soldier. We argue that largely hidden Muslim cemeteries throughout contemporary Spain, such as our case study in Barcia built during the Spanish Civil War, serve as a starting point for thinking about enduring spatial and cultural exclusions in Spain’s civil sphere: that is, those who are deemed civil or uncivil in both present and past, kept apart through their association with danger, threat, and deviance from Spanish values/norms. We further emphasize not only national but also regional social, cultural and political configurations that give shape to understandings of who belongs, both in life and after death. Drawing on ethnographic visits to the cemetery, interviews with local stakeholders in the cemetery, as well as local and regional archives, we develop a theory of multidirectional memory, that is: the overlap and interference of memories that help to constitute the public sphere, specifically by expanding the range of imagined life experiences for the members of a society—thereby expanding the imagined community in the present through recognition of a shared history.